2017
DOI: 10.3389/fmicb.2016.02133
|View full text |Cite|
|
Sign up to set email alerts
|

The Hog1 MAP Kinase Promotes the Recovery from Cell Cycle Arrest Induced by Hydrogen Peroxide in Candida albicans

Abstract: Eukaryotic cell cycle progression in response to environmental conditions is controlled via specific checkpoints. Signal transduction pathways mediated by MAPKs play a crucial role in sensing stress. For example, the canonical MAPKs Mkc1 (of the cell wall integrity pathway), and Hog1 (of the HOG pathway), are activated upon oxidative stress. In this work, we have analyzed the effect of oxidative stress induced by hydrogen peroxide on cell cycle progression in Candida albicans. Hydrogen peroxide was shown to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 78 publications
1
10
0
Order By: Relevance
“…Adhesion under flow was strongly reduced for the hog1∆ mutant. Interestingly, an earlier report showed that the hypha-specific cyclin Hgc1 was crucial for adhesion under flow conditions [30] and Hog1 has been implicated in the regulation of Hgc1 [33].…”
Section: Discussionmentioning
confidence: 99%
“…Adhesion under flow was strongly reduced for the hog1∆ mutant. Interestingly, an earlier report showed that the hypha-specific cyclin Hgc1 was crucial for adhesion under flow conditions [30] and Hog1 has been implicated in the regulation of Hgc1 [33].…”
Section: Discussionmentioning
confidence: 99%
“…Arana et al ( 2005 ) revealed that the human pathogen C. albicans lacking Pbs2 was defective in growth under hyperosmotic conditions mediated by sorbitol. Mkc1 is involved in the response to oxidative stress and cell wall integrity (Correia et al, 2017 ). And the Western blot signal of phosphorylated Mkc1 in response to hydrogen peroxide is reduced significantly in pbs2 mutants (Arana et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, MAPK signaling pathways are activated by many extracellular stimuli and mediate signal transduction from the cell surface to the nucleus (Monge et al, 2006 ). Four MAPK signaling pathways have been identified in C. albicans : the Mkc1 pathway, related to cell wall integrity (Navarro-García et al, 1995 ); the Hog1 pathway, mainly participating in osmotic, oxidative, and other stress adaptions (Smith et al, 2004 ; Correia et al, 2016 ); the Cek1 pathway, involved in mating and starvation (Csank et al, 1998 ; Chen et al, 2002 ); and the Cek2 pathway, crucial for mating (Chen et al, 2000 , 2002 ). Each of these MAPK signaling pathways plays important roles in the growth and virulence of C. albicans .…”
Section: Potential Antifungal Targets Within Hsps-associated Intracelmentioning
confidence: 99%